Targeting integrin α5β1 in urological tumors: opportunities and challenges - Zhou, Xuming; Zhu, Hezhen; Luo, Cong; Xiao, Huan; Zou, Xiaofeng; Zou, Junrong; Zhang, Guoxi (Frontiers in Oncology, 2023)
Urological tumors, such as prostate cancer, renal cell carcinoma, and bladder cancer, have shown a significant rise in prevalence in recent years and account for a significant proportion of malignant tumors. It has been established that metastasis to distant organs caused by urological tumors is the main cause of death, although the mechanisms underlying metastasis have not been fully elucidated. The fibronectin receptor Integrin α5β1 reportedly plays an important role in distant metastasis and is closely related to tumor development. It is widely thought to be an important cancer mediator by interacting with different ligands, mediating tumor adhesion, invasion, and migration, and leading to immune escape. In this paper, we expound on the relationship and regulatory mechanisms of integrin α5β1 in these three cancers. In addition, the clinical applications of integrin α5β1 in these cancers, especially against treatment resistance, are discussed. Last but not least, the possibility of integrin α5β1 as a potential target for treatment is examined, proposing new ideas for future research.